A comparative study of Labeo victorianus (Bouelenger, 1901) and Oreochromis niloticus (Linnaeus, 1758) grown in polyculture systems. Issue 1 (6th April 2018) - Orina, P. S.; Charo‐Karisa, H.; Munguti, J. M.; Boera, P.; Abwao, J.; Kyule, D.; Opiyo, M.; Marcial, H.; Manyala, J.; Rasowo, J. O.
Abstract: A polyculture experiment with African carp ( Labeo victorianus ) and Nile tilapia ( Oreochromis niloticus ) was conducted for 24 weeks in 12 earthen ponds measuring 150 m 2 to assess their compatibility. Monoculture treatments T1 and T4 for L. victorianus and O. niloticus, respectively, were the controls for the two species, while treatments T2 and T3 were a polyculture of L. victorianus and O. niloticus at a ratio of 1:2 and 2:1, respectively. All treatments were carried out in triplicate, with feedings performed twice daily at 09:00 hr and 16:00 hr at 10%, 5% and 3% body weight distributed evenly over the 24‐week growth period. Fish sampling was conducted monthly, while water quality was measured biweekly. Treatment T3 (1L: 2T) had a significantly ( p < .05) higher survival (L = 49% and T = 87%), compared to T2 (L = 31% and T = 69%, 2L: 1T). O. niloticus monoculture treatment (T4) exhibited a significantly higher survival ( p < .05) and higher growth (80%; 79 ± 20.04 g) than L. victorianus monoculture (T1) (50%; 13.12 ± 4.49 g). Dawn and afternoon temperatures ranged between 20.16–24.49°C and 23.76–31.07°C, respectively. The lowest temperatures were recorded in the months of June, July and August. The NH3 concentration was zero at 14:00 hr for all treatments throughout the growth period, but significantly higher ( p < .05) in T1 at 06:00 hr. The pH and DO levels at 06:00 hr and 14:00 hr were significantly different in all the treatments ( p < .05). The slow growth of L. victorianus can be associated with the low temperatures and DO levels. However, there is need to identify other factors that may have contributed to the poor growth of L. victorianus . Accordingly, this study recommends L. victorianus growth trials in other culture systems, coupled with different feed formulations, to identify optimal culture conditions.